How should we share research data? : Recommendations from the Norwegian committee on sharing and reuse of research data - Aronsen, Jan Magnus; Heggland, Ingrid; Tronstad, Stein; Pedersen, Ole Petter (Septentrio Conference Series, 2021)
See RECORDING. One of the central aspects of Open Science is to make research outputs accessible. From Open Access to scientific publications, the perspective has widened to also include other results, such as research data. Open Data is an important part of ensuring reproducible research, as well as enabling reuse of research data. When making research data publicly available, a licence should be applied, describing restrictions and permissions for reuse. But how do you decide what licence to use for research data, to ensure that it is “As open as possible, as closed as necessary”? Who has the rights to research data in publicly funded research? What data should be published, and what data needs to be kept confidential? In 2020, the Ministry of Education and Research asked the Research Council of Norway and UNIT to set up a committee to examine issues related to rights and licensing of research data. In this presentation, members of the committee will highlight and discuss some of the recommendations in the final report. To ensure Open and FAIR research data, the legal aspects must be clarified. In addition, the committee has highlighted several other aspects that need to be addressed in order to achieve more sharing and reuse of research data, including funding incentives, infrastructure and tools, as well as resources and competence.